Researching Complex Interventions in Health: The State of the Art. Issue 1 (April 2016) - Craig, Peter; Rahm-Hallberg, Ingalill; Britten, Nicky; Borglin, Gunilla; Meyer, Gabriele; Köpke, Sascha; Noyes, Jane; Chandler, Jackie; Levati, Sara; Sales, Anne; Thabane, Lehana; Giangregorio, Lora; et al.
Table of contents KEYNOTE PRESENTATIONS K1 Researching complex interventions: the need for robust approaches Peter Craig K2 Complex intervention studies: an important step in developing knowledge for practice Ingalill Rahm-Hallberg K3 Public and patient involvement in research: what, why and how? Nicky Britten K4 Mixed methods in health service research – where do we go from here? Gunilla Borglin SPEAKER PRESENTATIONS S1 Exploring complexity in systematic reviews of complex interventions Gabriele Meyer, Sascha Köpke, Jane Noyes, Jackie Chandler S2 Can complex health interventions be optimised before moving to a definitive RCT? Strategies and methods currently in use Sara Levati S3 A systematic approach to develop theory based implementation interventions Anne Sales S4 Pilot studies and feasibility studies for complex interventions: an introduction Lehana Thabane, Lora Giangregorio S5 What can be done to pilot complex interventions? Nancy Feeley, Sylvie Cossette S6 Using feasibility and pilot trials to test alternative methodologies and methodological procedures prior to full scale trials Rod Taylor S7 A mixed methods feasibility study in practice Jacqueline Hill, David A Richards, Willem Kuyken S8 Non-standard experimental designs and preference designs Louise von Essen S9 Evaluation gone wild: using natural experimental approaches to evaluate complex interventions Andrew Williams S10 The stepped wedge cluster randomised trial: an opportunity to increase the quality of evaluations of service delivery and public policy interventions Karla Hemming, Richard Lilford, Alan Girling, Monica Taljaard S11 Adaptive designs in confirmatory clinical trials: opportunities in investigating complex interventions Munyaradzi Dimairo S12 Processes, contexts and outcomes in complex interventions, and the implications for evaluation Mark Petticrew S13 Processes, contexts and outcomes in complex interventions, and the implications for evaluation Janis Baird, Graham Moore S14 Qualitative evaluation alongside RCTs: what to consider to get relevant and valuable results Willem Odendaal, Salla Atkins, Elizabeth Lutge, Natalie Leon, Simon Lewin S15 Using economic evaluations to understand the value of complex interventions: when maximising health status is not sufficient Katherine Payne S16 How to arrive at an implementation plan Theo van Achterberg S17 Modelling process and outcomes in complex interventions Walter Sermeus S18 Systems modelling for improving health care Martin Pitt, Thomas Monks